A high-performance polymer foamable modified asphalt and preparation method thereof

By combining high-performance polymers with asphalt and using modified resins and fillers to form specific structures, the problems of poor mechanical properties and insufficient functions of traditional modified asphalt at extreme temperatures are solved, and the comprehensive performance improvement of high-performance asphalt is achieved.

CN119775790APending Publication Date: 2025-04-08JIANGSU POLARIS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046971.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional modified asphalt has poor mechanical properties under extreme temperature conditions, and has insufficient stain resistance and waterproof functions, making it difficult to meet the high-performance needs of modern transportation and construction infrastructure.

Method used

The combination of high-performance polymers and asphalt is used to form a tightly connected molecular chain connection system and barrier structure through the combination of modified resin and filler, thereby improving the mechanical properties, temperature tolerance and waterproof properties of asphalt.

Benefits of technology

It realizes the excellent mechanical and mechanical properties of asphalt, temperature resistance and good stain resistance and waterproof functions, and meets the high-performance needs of modern transportation and construction infrastructure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238754980000141
    Figure BDA0005238754980000141
  • Figure BDA0005238754980000151
    Figure BDA0005238754980000151
Patent Text Reader

Abstract

The present application relates to the field of asphalt materials, and in particular to a high-performance polymer foamable modified asphalt and a preparation method thereof. The high-performance polymer foamable modified asphalt, in parts by mass, has the following raw materials: 60 to 80 parts of base asphalt, 15 to 22 parts of modified polymer, 5 to 10 parts of adhesive resin, 3 to 6 parts of foaming agent, 3 to 8 parts of plasticizer, 2 to 3 parts of stabilizer, 0.5 to 1.2 parts of rheology regulator, 10 to 15 parts of filler, and 0.8 to 1.6 parts of anti-settling agent. The foamable modified asphalt finally obtained can not only have excellent mechanical properties, but also maintain high tolerance to temperature changes, and at the same time retain good functional properties such as stain resistance and waterproofing, has very excellent comprehensive performance, can effectively meet the comprehensive performance requirements of existing transportation and construction infrastructure for road paving and conventional building materials, and has a very broad application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt materials, and in particular to a high-performance polymer foamable modified asphalt and a preparation method thereof. Background Art

[0002] With the development of modern transportation and construction infrastructure, the requirements for road paving and conventional building materials are getting higher and higher, and traditional petroleum asphalt is limited by its own performance and cannot meet more construction requirements. In order to overcome these problems, researchers have introduced various types of polymers to modify asphalt to improve its comprehensive performance. However, even after the above modification, traditional modified asphalt still has some limitations, especially in dealing with extreme temperature changes, high-load traffic pressure and complex outdoor environmental conditions.

[0003] In recent years, with the enhancement of environmental awareness and technological progress, foamable asphalt has gradually attracted attention as a new type of road paving material. Through appropriate process treatment, tiny bubbles can be introduced into the asphalt to form a lightweight and elastic foam structure, which can not only effectively alleviate the noise generated during vehicle driving, but also has excellent heat insulation effect, and to a certain extent improves the road surface's anti-deformation ability and self-repair properties. In order to further improve the performance of foamable asphalt, researchers have begun to explore new ways to combine high-performance polymers with asphalt. Such high-performance polymers include not only conventional thermoplastic or thermosetting resins, but also nanomaterials with special functions, fiber-reinforced materials, etc.

[0004] Although existing technologies have made certain progress, they still face the following challenges in practical applications. For example, even after modification, ordinary asphalt still exhibits poor mechanical properties under extreme temperature conditions, affecting its safety and reliability in long-term service. Insufficient functionality, such as stain resistance and waterproofing, needs to be further enhanced.

[0005] Therefore, in order to solve the above-mentioned problems, the present application provides a high-performance polymer foamable modified asphalt and a preparation method thereof. The foamable modified asphalt finally obtained not only has excellent mechanical properties, but also can maintain high tolerance to temperature changes, and at the same time retains good functional properties such as stain resistance and waterproofness. It has very excellent comprehensive performance, can effectively meet the comprehensive performance requirements of existing transportation and construction infrastructure for road paving and conventional building materials, and has a very broad application prospect. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a high-performance polymer foamable modified asphalt. The raw materials are, by mass, 60 to 80 parts of base asphalt, 15 to 22 parts of modified polymer, 5 to 10 parts of adhesive resin, 3 to 6 parts of foaming agent, 3 to 8 parts of plasticizer, 2 to 3 parts of stabilizer, 0.5 to 1.2 parts of rheology regulator, 10 to 15 parts of filler, and 0.8 to 1.6 parts of anti-settling agent.

[0007] As a preferred solution, the base asphalt is AH-90 petroleum asphalt or AH-70 petroleum asphalt.

[0008] As a preferred solution, the mass ratio of the base asphalt, the modified polymer and the adhesive resin is (65-75):(16-20):(6-8).

[0009] As a preferred solution, the mass ratio of the base asphalt, the modified polymer and the adhesive resin is (70-74): (17-19): (6.5-7.5).

[0010] As a preferred solution, the mass ratio of the base asphalt and the filler is (65-75):(11-15).

[0011] As a preferred solution, the mass ratio of the base asphalt and the filler is (70-74): (12-13).

[0012] As a preferred solution, the preparation method of the modified resin specifically includes the following steps: S1: adding cyclohexyl methacrylate, 2-ethylhexyl acrylate, isooctyl acrylate, perfluorobutyl ethyl acrylate and 3-aminopropyl triethoxysilane to deionized water, then adding fatty alcohol polyoxyethylene ether, stirring and mixing at a speed of 200-300 rpm until a uniform pre-emulsion is formed; S2: taking 10wt% of the pre-emulsion and adding it to deionized water, then adding ammonium persulfate, heating to 75-80°C and keeping the temperature for reaction for 0.5-1h; S3: adding N-hydroxymethyl acrylamide and adding ammonium persulfate for a second time, and dropping the remaining pre-emulsion into the reaction system, the dropping time is 1-2h, and after the dropping is completed, the temperature is kept for reaction for 4-5h; S4: after the reaction is completed, the system is naturally cooled to room temperature, then filtered through a 400-500 mesh sieve to remove large particles, and kept warm and sealed to obtain the product.

[0013] As a preferred solution, the mass ratio of cyclohexyl methacrylate, 2-ethylhexyl acrylate, isooctyl acrylate, perfluorobutyl ethyl acrylate and 3-aminopropyltriethoxysilane is (15-20): (6-8): (2-2.5): (2.5-3): (0.2-0.4).

[0014] As a preferred solution, the mass ratio of cyclohexyl methacrylate to N-hydroxymethyl acrylamide is (15-20):(45-55).

[0015] The modified resin added in the present application can form a tightly connected molecular chain connection system in the asphalt system, and its multi-segment and long-segment structures can serve as extension carriers for asphalt particles in the asphalt system, greatly improving the extension and dispersion effects of the asphalt particles while avoiding the aggregation effect of a large number of particles, thereby ensuring the overall performance of the asphalt system and the stability of the mechanical properties; on the other hand, the addition of the modified resin in combination with the added filler can achieve a barrier effect on water molecules and active molecules within the system, greatly improving the penetration and movement resistance and path length of water molecules in the internal system, and reducing the frequency of mutual contact between active molecules, thereby limiting the movement of water molecules internally and avoiding the formation of a continuous transport chain, thereby obtaining excellent temperature tolerance and waterproof properties, and by acting as a flow carrier for the modified particles in the filler, helping to improve stain resistance.

[0016] As a preferred solution, the adhesive resin is at least one of polyethylene, SIS, SBS, EVA, C5 petroleum resin and C9 petroleum resin.

[0017] As a preferred solution, the adhesive resin is a composition of polyethylene and SBS.

[0018] As a preferred solution, the mass ratio of polyethylene to SBS is (0.8-1.5):(3-4.5).

[0019] As a preferred solution, the mass ratio of polyethylene to SBS is (1.2-1.4):(3.8-4.2).

[0020] As a preferred solution, the foaming agent is a combination of citrate and citric acid.

[0021] As a preferred solution, the mass ratio of the citrate to citric acid is (1-1.2):(1.5-2).

[0022] As a preferred solution, the plasticizer is at least one of dioctyl phthalate, dibutyl phthalate, dioctyl adipate, diisononyl adipate and epoxidized soybean oil.

[0023] As a preferred solution, the plasticizer is dioctyl phthalate.

[0024] As a preferred solution, the stabilizer is at least one of salicylates, benzotriazoles, organosiloxanes, hindered amines and benzophenones.

[0025] As a preferred solution, the stabilizer is an organosiloxane or a hindered amine.

[0026] As a preferred solution, the rheology regulator is polyamide wax or hydrogenated rosin resin.

[0027] As a preferred solution, the rheology regulator is polyamide wax.

[0028] As a preferred solution, the anti-settling agent is at least one of cellulose ether, polyvinyl alcohol, organic bentonite and modified starch.

[0029] As a preferred solution, the anti-settling agent is a composition of cellulose ether and polyvinyl alcohol.

[0030] As a preferred solution, the mass ratio of the cellulose ether to the polyvinyl alcohol is (1-1.2):(2-2.5).

[0031] As a preferred solution, the cellulose ether is at least one of sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and methyl cellulose.

[0032] As a preferred solution, the cellulose ether is hydroxyethyl cellulose.

[0033] As a preferred solution, the filler is a combination of talc and modified nanoparticles.

[0034] As a preferred solution, the mass ratio of the talc powder to the modified nanoparticles is (6-8):(3-5).

[0035] As a preferred scheme, the preparation method of the modified nanoparticles specifically includes the following steps: S1: zinc oxide and aluminum chloride are mixed and added to deionized water, and then glutaric anhydride is added and the temperature is raised to 60-65°C and kept warm for 2-3 hours; S2: ethyl orthosilicate and DMF solution are then added, and after mixing and stirring evenly, terephthalic acid, p-aminobenzoic acid and 2-methylimidazole are added, and then hydrochloric acid is added to adjust the pH to 5.5-6; S3: the temperature is raised to 120-125°C, and the temperature is kept for reaction for 18-22 hours. After the reaction is completed, the temperature is naturally lowered to room temperature, and sodium hydroxide is added to adjust the pH to 7-7.2, and then the solid product is obtained by centrifugation after stirring at a speed of 120-180 rpm for 15-20 minutes, and then the solid product is obtained by centrifugation. The solid product is washed with DMF 2-3 times and vacuum dried at 80-85°C overnight.

[0036] As a preferred solution, the mass ratio of zinc oxide to glutaric anhydride is (0.4-0.6):(0.1-0.15).

[0037] As a preferred solution, the mass ratio of zinc oxide, aluminum chloride, tetraethyl orthosilicate, terephthalic acid, p-aminobenzoic acid and 2-methylimidazole is (0.4-0.6):(3-3.5):(0.2-0.25):(1.2-1.4):(0.4-0.5):(0.2-0.25).

[0038] As a preferred solution, the average particle size of the zinc oxide is 10 to 20 nm.

[0039] As a preferred solution, the average particle size of the modified nanoparticles is 450-600 nm.

[0040] The special composite structure of the modified nanoparticles can form good adhesion with the resin system through the surface particles in the asphalt system, while achieving the function of guiding the internal trace moisture, and then absorbing and removing the internal moisture through the internal micropore adsorption after guidance, thereby obtaining excellent water resistance. On the other hand, the good electron circulation flow structure formed by the modified nanoparticles can greatly improve the maintenance strength of the oxidation molecules of the surface zinc oxide particles, and then effectively oxidize and decompose the organic pollutants on the surface during long-term use, thereby obtaining a good anti-fouling effect.

[0041] The second aspect of the present application provides a method for preparing the above-mentioned high-performance polymer foamable modified asphalt, which specifically includes the following steps: S1: Add the base asphalt into a mixing container, heat it to 140-160°C, then add the modified polymer, adhesive resin and filler, and mix and stir at 300-400rpm for 30-40min; S2: After stirring, reduce the stirring speed to 120-180rpm, slowly add the foaming agent and plasticizer, continue stirring for 10-20min, then add the remaining raw materials and stir for 20-40min until all the ingredients are completely fused; S3: After fusion, cool the mixture to below the safe handling temperature, and then store it in a sealed container to prevent premature foaming. When in use, inject an appropriate amount of water to initiate the foaming process, and finally lay and compact.

[0042] The beneficial effects of this application are:

[0043] 1. The high-performance polymer foamable modified asphalt provided in the present application not only has excellent mechanical properties, but also can maintain high tolerance to temperature changes, and at the same time retains good functional properties such as good stain resistance and waterproofness. It has very excellent comprehensive performance, can effectively meet the comprehensive performance requirements of existing transportation and construction infrastructure for road paving and conventional building materials, and has a very broad application prospect.

[0044] 2. A high-performance polymer foamable modified asphalt provided in the present application, the added modified resin can form a tightly connected molecular chain connection system in the asphalt system, and its multi-segment and long-chain segment structure can serve as an extension carrier for asphalt particles in the asphalt system, greatly improving the extension and dispersion effect of the asphalt particles while avoiding the aggregation effect of a large number of particles, thereby ensuring the overall performance of the asphalt system and the stability of the mechanical properties.

[0045] 3. A high-performance polymer foamable modified asphalt provided in the present application, the added modified resin and the added filler can achieve a barrier effect on water molecules and active molecules inside the system, greatly improve the penetration movement resistance and path length of water molecules in the internal system, and reduce the frequency of mutual contact between active molecules, thereby limiting the movement of water molecules inside and avoiding them from forming a continuous transport chain, thereby obtaining excellent temperature tolerance and waterproof properties, and helping to improve stain resistance by acting as a flow carrier for the modified particles in the filler.

[0046] 4. The high-performance polymer foamable modified asphalt provided in the present application has a special composite structure of modified nanoparticles added, which can form good adhesion with the resin system through the surface particles in the asphalt system, while achieving the guiding effect for the internal trace moisture, and then after the guidance, the internal moisture is absorbed and removed through the internal micropore adsorption, thereby obtaining excellent water resistance. On the other hand, the good electron circulation flow structure formed by the modified nanoparticles can greatly improve the maintenance strength of the oxidation molecules of the surface zinc oxide particles, and then effectively oxidize and decompose the organic pollutants on the surface during long-term use, thereby obtaining a good anti-fouling effect. DETAILED DESCRIPTION

[0047] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0048] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0049] Example 1

[0050] Example 1 The first aspect provides a high-performance polymer foamable modified asphalt. The raw materials, calculated by mass, are: 72.4 parts of base asphalt, 18.6 parts of modified polymer, 6.8 parts of adhesive resin, 4.2 parts of foaming agent, 6.5 parts of plasticizer, 2.2 parts of stabilizer, 0.8 parts of rheology regulator, 12.2 parts of filler, and 1.4 parts of anti-settling agent.

[0051] The base asphalt is AH-70 petroleum asphalt.

[0052] The preparation method of the modified resin specifically includes the following steps, calculated by mass: S1: 18.6 parts of cyclohexyl methacrylate, 6.5 parts of 2-ethylhexyl acrylate, 2.2 parts of isooctyl acrylate, 2.8 parts of perfluorobutyl ethyl acrylate and 0.32 parts of 3-aminopropyl triethoxysilane are mixed and added to 150 parts of deionized water, and then 0.2 parts of fatty alcohol polyoxyethylene ether AEO-9 are added, and the mixture is stirred at a speed of 220 rpm until a uniform pre-emulsion is formed; S2: Take 10wt% of the pre-emulsion is added to 200 parts of deionized water, and then 0.02 parts of ammonium persulfate are added, and the temperature is raised to 80°C for reaction for 1 hour; S3: 52 parts of N-hydroxymethyl acrylamide and 0.14 parts of ammonium persulfate are added twice, and the remaining pre-emulsion is added dropwise to the reaction system for 1.5 hours. After the addition is completed, the reaction is continued for 4 hours; S4: After the reaction is completed, the system is naturally cooled to room temperature, and then filtered through a 450-mesh sieve to remove large particles, and the system is kept warm and sealed to obtain the product.

[0053] The adhesive resin is a composition of polyethylene and SBS, and the mass ratio of the two is 1.3:4.

[0054] Polyethylene was purchased from ExxonMobil Corporation of the United States as Exact 4051 product; SBS was purchased from Sinopec as YH-793 product.

[0055] The foaming agent is a composition of citrate and citric acid, and the mass ratio of the two is 1:1.8.

[0056] The plasticizer is dioctyl phthalate; the stabilizer is a hindered amine, Tinuvin 292 model product purchased from BASF, Germany.

[0057] The rheology modifier was polyamide wax, purchased from Zhejiang Fenghong New Materials Co., Ltd., China, and sold as model PA-630.

[0058] The anti-settling agent is a composition of hydroxyethyl cellulose and polyvinyl alcohol PVA-2488, and the mass ratio of the two is 1.1:2.4.

[0059] The filler is a composition of talc powder and modified nanoparticles, and the mass ratio of the two is 7:4.

[0060] The preparation method of modified nanoparticles specifically includes the following steps, calculated by mass: S1: 0.48 parts of zinc oxide and 3.4 parts of aluminum chloride are mixed and added to 120 parts of deionized water, and then 0.14 parts of glutaric anhydride are added and the temperature is raised to 65°C and kept warm for 2.5 hours; S2: 0.22 parts of ethyl orthosilicate and 200 parts of DMF solution are added, and after mixing and stirring evenly, 1.3 parts of terephthalic acid, 0.45 parts of p-aminobenzoic acid and 0.23 parts of 2-methylimidazole are added, and then hydrochloric acid is added to adjust the pH to 6; S3: the temperature is raised to 120°C, and the temperature is kept for reaction for 20 hours. After the reaction is completed, the temperature naturally drops to room temperature, and sodium hydroxide is added to adjust the pH to 7.2, and then the solid product is obtained by centrifugation after stirring at a speed of 160 rpm for 20 minutes, and the solid product is washed 3 times with DMF and vacuum dried at 80°C overnight.

[0061] The average particle size of zinc oxide is 16 nm and the average particle size of modified nanoparticles is 510 nm.

[0062] The second aspect of this embodiment provides a method for preparing the above-mentioned high-performance polymer foamable modified asphalt, which specifically includes the following steps: S1: Add the base asphalt into a mixing container, heat it to 150°C, then add the modified polymer, adhesive resin and filler and mix and stir at 350rpm for 35min; S2: After stirring, reduce the stirring speed to 160rpm, slowly add the foaming agent and plasticizer, continue stirring for 15min, then add the remaining raw materials and stir for 30min until all the ingredients are completely fused; S3: After fusion, cool the mixture to below the safe handling temperature, and then store it in a sealed container to prevent premature foaming. When in use, inject an appropriate amount of water to initiate the foaming process, and finally lay and compact.

[0063] Example 2

[0064] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the high-performance polymer foamable modified asphalt, in parts by mass, has the following raw materials: 68.5 parts of base asphalt, 19.8 parts of modified polymer, 7.8 parts of adhesive resin, 4.4 parts of foaming agent, 6.8 parts of plasticizer, 2.4 parts of stabilizer, 0.7 parts of rheology regulator, 14.5 parts of filler, and 1.2 parts of anti-settling agent.

[0065] The adhesive resin is a composition of polyethylene and SBS, and the mass ratio of the two is 0.8:4.5.

[0066] The anti-settling agent is a composition of hydroxyethyl cellulose and polyvinyl alcohol PVA-2488, and the mass ratio of the two is 1:2.5.

[0067] The filler is a composition of talc powder and modified nanoparticles, and the mass ratio of the two is 8:3.

[0068] Example 3

[0069] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the high-performance polymer foamable modified asphalt, in parts by mass, has the following raw materials: 75 parts of base asphalt, 16.2 parts of modified polymer, 6 parts of adhesive resin, 4.3 parts of foaming agent, 6.8 parts of plasticizer, 2.4 parts of stabilizer, 0.7 parts of rheology regulator, 11 parts of filler, and 1.2 parts of anti-settling agent.

[0070] The adhesive resin is a composition of polyethylene and SBS, and the mass ratio of the two is 1.5:3.2.

[0071] The anti-settling agent is a composition of hydroxyethyl cellulose and polyvinyl alcohol PVA-2488, and the mass ratio of the two is 1.2:2.

[0072] The filler is a composition of talcum powder and modified nanoparticles, and the mass ratio of the two is 6:5.

[0073] Comparative Example 1

[0074] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the high-performance polymer foamable modified asphalt, in parts by mass, has the following raw materials: 85 parts of base asphalt, 5.5 parts of modified polymer, 6.8 parts of adhesive resin, 4.2 parts of foaming agent, 6.5 parts of plasticizer, 2.2 parts of stabilizer, 0.8 parts of rheology regulator, 14.2 parts of filler, and 1.4 parts of anti-settling agent.

[0075] Comparative Example 2

[0076] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the high-performance polymer foamable modified asphalt, in parts by mass, has the following raw materials: 80 parts of base asphalt, 22.2 parts of modified polymer, 6.8 parts of adhesive resin, 4.2 parts of foaming agent, 6.5 parts of plasticizer, 2.2 parts of stabilizer, 0.8 parts of rheology regulator, 4.5 parts of filler, and 1.4 parts of anti-settling agent.

[0077] Comparative Example 3

[0078] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin specifically comprises the following steps, calculated by mass: S1: 5.5 parts of cyclohexyl methacrylate, 1.2 parts of 2-ethylhexyl acrylate, 1.8 parts of isooctyl acrylate, 0.5 parts of perfluorobutyl ethyl acrylate and 0.12 parts of 3-aminopropyl triethoxysilane are mixed and added to 150 parts of deionized water, and then 0.2 parts of fatty alcohol polyoxyethylene ether AEO-9 are added, and the mixture is stirred at a speed of 220 rpm. until a uniform pre-emulsion is formed; S2: take 10wt% of the pre-emulsion and add it to 200 parts of deionized water, then add 0.02 parts of ammonium persulfate, heat to 80°C and keep warm for reaction for 1 hour; S3: add 75 parts of N-hydroxymethyl acrylamide and add 0.14 parts of ammonium persulfate for the second time, and add the remaining pre-emulsion dropwise to the reaction system, the dropping time is 1.5 hours, and after the dropping is completed, continue to keep warm for 4 hours; S4: after the reaction is completed, cool the system naturally to room temperature, then filter with a 450-mesh sieve to remove large particles, keep warm and seal, and obtain.

[0079] Comparative Example 4

[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 40 nm and the average particle size of the modified nanoparticles is 700 nm.

[0081] Comparative Example 5

[0082] The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a composition of talcum powder and modified nanoparticles, and the mass ratio of the two is 9:1.

[0083] Comparative Example 6

[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles specifically includes the following steps, calculated by mass: S1: 0.12 parts of zinc oxide and 6.5 parts of aluminum chloride are mixed and added to 120 parts of deionized water, and then 0.14 parts of glutaric anhydride are added and the temperature is raised to 65°C and kept warm for 2.5 hours; S2: 0.22 parts of ethyl orthosilicate and 200 parts of DMF solution are added, and after mixing and stirring evenly, 2.5 parts of terephthalic acid, 0.95 parts of p-aminobenzoic acid and 0.05 parts of 2-methylimidazole are added, and then hydrochloric acid is added to adjust the pH to 6; S3: the temperature is raised to 120°C, and the reaction is kept warm for 20 hours. After the reaction is completed, it naturally drops to room temperature, and sodium hydroxide is added to adjust the pH to 7.2, and then stirred at 160 rpm for 20 minutes, and then centrifuged to obtain a solid product, and the solid product is washed 3 times with DMF and vacuum dried at 80°C overnight.

[0085] Comparative Example 7

[0086] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles specifically includes the following steps, calculated by mass: S1: 1.2 parts of zinc oxide and 3 parts of aluminum chloride are mixed and added to 120 parts of deionized water, and then 0.14 parts of glutaric anhydride are added and the temperature is raised to 65°C and kept warm for 2.5 hours; S2: 0.22 parts of ethyl orthosilicate and 200 parts of DMF solution are added, and after mixing and stirring evenly, 1.1 parts of terephthalic acid, 0.6 parts of p-aminobenzoic acid and 1.1 parts of 2-methylimidazole are added, and then hydrochloric acid is added to adjust the pH to 6; S3: the temperature is raised to 120°C, and the reaction is kept warm for 20 hours. After the reaction is completed, it naturally drops to room temperature, and sodium hydroxide is added to adjust the pH to 7.2, and then stirred at 160 rpm for 20 minutes, and then centrifuged to obtain a solid product, and the solid product is washed 3 times with DMF and vacuum dried at 80°C overnight.

[0087] Performance Evaluation

[0088] Needle penetration and softening point: The polymer modified asphalt prepared in the examples and comparative examples was tested for needle penetration, with reference to standard JTG / T 3364-02-2019, and the average values ​​of the measured values ​​were recorded in Table 1.

[0089] Heat stability: The polymer modified asphalt prepared in the examples and comparative examples was tested for heat stability. The polymer modified asphalt was kept in a constant temperature box at 75% humidity and 110°C for 3 days and then taken out to observe its phase separation, segregation and dispersion state. If the asphalt showed obvious phase separation, segregation and inability to disperse, it was recorded as unqualified, otherwise it was qualified. The qualified percentage of 50 tests was recorded in Table 1.

[0090] Water resistance test: Referring to the T0729-2000 standard, the modified asphalt prepared in the embodiment and the comparative example was subjected to a water immersion Marshall test to obtain the residual stability after 48 hours. The test value was the average value of 10 tests and recorded in Table 1.

[0091] Stain resistance: The modified asphalt obtained in the examples and comparative examples was tested for stain resistance by a method similar to that of reference standard GB / T 9780-2013. The test pollutants were mineral oil and animal fat. After the test, the color difference value (ΔE*) of the test area was taken. If ΔE*≤0.5, it was considered qualified, otherwise it was unqualified. The qualified percentage of 50 tests was recorded in Table 1.

[0092] Table 1 Performance test results

[0093]

[0094]

[0095] From the final data results in Table 1, it can be seen that Examples 1 to 3 of the present application have better technical effects in terms of needle penetration, waterproof performance, temperature stability and stain resistance than Comparative Examples 1 to 7. This is mainly due to the combined effect of the modified functional resin and modified nanoparticles specified in the present application and other matching schemes. Comparative Examples 1 to 7 do not use specific modified functional resins and modified nanoparticles, which makes it impossible to effectively form a stable cross-linked network in the asphalt system, limits the extension of asphalt particles, aggravates the agglomeration phenomenon between large particles, and most importantly, cannot effectively inhibit the penetration of water molecules and active molecules in the asphalt system, thereby obtaining worse performance.

Claims

1. A high performance polymer foamable modified asphalt, characterized in that: High-performance polymer foamable modified asphalt, calculated by weight, the raw materials are: 60-80 parts of base asphalt, 15-22 parts of modified polymer, 5-10 parts of adhesive resin, 3-6 parts of foaming agent, 3-8 parts of plasticizer, 2-3 parts of stabilizer, 0.5-1.2 parts of rheology regulator, 10-15 parts of filler, and 0.8-1.6 parts of anti-settling agent; The base asphalt is AH-90 petroleum asphalt or AH-70 petroleum asphalt; The preparation method of the modified resin specifically comprises the following steps: S1: adding cyclohexyl methacrylate, 2-ethylhexyl acrylate, isooctyl acrylate, perfluorobutyl ethyl acrylate and 3-aminopropyl triethoxysilane to deionized water, then adding fatty alcohol polyoxyethylene ether, stirring and mixing at a speed of 200-300 rpm until a uniform pre-emulsion is formed; S2: taking 10wt% of the pre-emulsion and adding it to deionized water, then adding ammonium persulfate, heating to 75-80°C and keeping the temperature for reaction for 0.5-1h; S3: adding N-hydroxymethyl acrylamide and adding ammonium persulfate for a second time, and dropping the remaining pre-emulsion into the reaction system, the dropping time is 1-2h, and the keeping temperature for reaction is continued for 4-5h after the dropping is completed; S4: after the reaction is completed, the system is naturally cooled to room temperature, then filtered through a 400-500 mesh sieve to remove large particles, and kept warm and sealed to obtain the product; The mass ratio of cyclohexyl methacrylate, 2-ethylhexyl acrylate, isooctyl acrylate, perfluorobutyl ethyl acrylate and 3-aminopropyltriethoxysilane is (15-20): (6-8): (2-2.5): (2.5-3): (0.2-0.4); The mass ratio of cyclohexyl methacrylate to N-hydroxymethyl acrylamide is (15-20): (45-55); The adhesive resin is at least one of polyethylene, SIS, SBS, EVA, C5 petroleum resin and C9 petroleum resin.

2. The high performance polymer foamable modified asphalt according to claim 1, characterized in that: The mass ratio of the base asphalt, the modified polymer and the adhesive resin is (65-75):(16-20):(6-8).

3. The high performance polymer foamable modified asphalt according to claim 2, characterized in that: The mass ratio of the matrix asphalt to the filler is (65-75):(11-15).

4. The high performance polymer foamable modified asphalt according to claim 3, characterized in that: The adhesive resin is a composition of polyethylene and SBS; the mass ratio of the polyethylene to the SBS is (0.8-1.5): (3-4.5).

5. The high performance polymer foamable modified asphalt according to claim 4, characterized in that: The foaming agent is a combination of citrate and citric acid; the mass ratio of the citrate to the citric acid is (1-1.2): (1.5-2).

6. The high performance polymer foamable modified asphalt according to claim 5, characterized in that: The plasticizer is at least one of dioctyl phthalate, dibutyl phthalate, dioctyl adipate, diisononyl adipate and epoxidized soybean oil.

7. The high performance polymer foamable modified asphalt according to claim 6, characterized in that: The rheology regulator is polyamide wax or hydrogenated rosin resin.

8. The high performance polymer foamable modified asphalt according to claim 7, characterized in that: The filler is a composition of talcum powder and modified nanoparticles; the mass ratio of the talcum powder to the modified nanoparticles is (6-8): (3-5).

9. The high performance polymer foamable modified asphalt according to claim 8, characterized in that: The preparation method of the modified nanoparticles specifically comprises the following steps: S1: zinc oxide and aluminum chloride are mixed and added to deionized water, and then glutaric anhydride is added and the temperature is raised to 60-65° C. and kept warm for 2-3 hours; S2: ethyl orthosilicate and DMF solution are added, mixed and stirred evenly, and then terephthalic acid, p-aminobenzoic acid and 2-methylimidazole are added, and then hydrochloric acid is added to adjust the pH to 5.5-6; S3: the temperature is raised to 120-125° C., and the temperature is kept for reaction for 18-22 hours, and the temperature is naturally lowered to room temperature after the reaction is completed, and sodium hydroxide is added to adjust the pH to 7-7.2, and then the solid product is obtained by centrifugation and filtration after stirring at a speed of 120-180 rpm for 15-20 minutes, and then the solid product is washed with DMF for 2-3 times, and vacuum dried at 80-85° C. overnight to obtain the solid product; The mass ratio of zinc oxide to glutaric anhydride is (0.4-0.6): (0.1-0.15); The mass ratio of zinc oxide, aluminum chloride, tetraethyl orthosilicate, terephthalic acid, p-aminobenzoic acid and 2-methylimidazole is (0.4-0.6): (3-3.5): (0.2-0.25): (1.2-1.4): (0.4-0.5): (0.2-0.25); The average particle size of the zinc oxide is 10 to 20 nm.

10. A method for preparing the high performance polymer foamable modified asphalt according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Add the base asphalt into the mixing container, heat it to 140-160°C, then add the modified polymer, adhesive resin and filler and mix and stir at 300-400rpm for 30-40min; S2: After stirring, reduce the stirring speed to 120-180rpm, slowly add the foaming agent and plasticizer, continue stirring for 10-20min, then add the remaining raw materials and stir for 20-40min until all the ingredients are completely blended; S3: After fusion, cool the mixture to below the safe handling temperature, and then store it in a sealed container to prevent premature foaming. When using, inject an appropriate amount of water to initiate the foaming process, and finally lay and compact.